Dampak Program Orientasi Terhadap Adaptasi Tenaga Kependidikan Baru di Sekolah Menengah Kejuruan Plus Al Mujahidi - Muhammad Rijalus Sholihin; Taufiq Akbar; Siswanto Siswanto; Esha Latifatuz Zahro Zulkurnia; Salamun Salamun (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the impact of the orientation program on the adaptation of new education personnel at SMK Plus Al Mujahidi, Tembokrejo Village, Gumukmas District, Jember Regency. The research background is based on the importance of the role of education personnel in supporting the smooth administration and education services, where the adaptation process is one of the main challenges for new employees. The orientation program is seen as a strategic step to introduce the main tasks, work culture, and school administration system, so that new personnel can adapt faster. The research method uses a descriptive qualitative approach with data collection techniques in the form of in-depth interviews and observations. The results of the study showed that orientation significantly contributed to five aspects of adaptation of new education personnel, namely understanding duties and roles, adjustment of work culture, administrative mastery, social relations with seniors, and self-confidence. Field data showed an 85% increase in role understanding, a 70% increase in work culture adjustment, and a 35% decrease in administrative errors after orientation. However, social adaptation with senior colleagues still requires further coaching. Overall, this study emphasizes that structured orientation programs are an important instrument in strengthening the adaptation of new education personnel, and are relevant to be applied in improving the quality of human resources in educational institutions